An EAR-Dependent Regulatory Module Promotes Male Germ Cell Division and Sperm Fertility in Arabidopsis . Issue 5 (29th May 2014) - Borg, Michael; Rutley, Nicholas; Kagale, Sateesh; Hamamura, Yuki; Gherghinoiu, Mihai; Kumar, Sanjeev; Sari, Ugur; Esparza-Franco, Manuel A.; Sakamoto, Wataru; Rozwadowski, Kevin; Higashiyama, Tetsuya; Twell, David
Abstract : The development of sperm cells in angiosperms is coordinated by the MYB transcription factor DUO1. Male germ cell division and sperm fertility are shown to depend on DAZ1 and DAZ2, two zinc finger proteins regulated by DUO1, which physically interact with the corepressor TOPLESS. The DUO1-DAZ1/DAZ2 regulatory module thus implicates repressive mechanisms in plant sperm cell development. Abstract: The production of the sperm cells in angiosperms requires coordination of cell division and cell differentiation. In Arabidopsis thaliana, the germline-specific MYB protein DUO1 integrates these processes, but the regulatory hierarchy in which DUO1 functions is unknown. Here, we identify an essential role for two germline-specific DUO1 target genes, DAZ1 and DAZ2, which encode EAR motif–containing C2 H2 -type zinc finger proteins. We show that DAZ1/DAZ2 are required for germ cell division and for the proper accumulation of mitotic cyclins. Importantly, DAZ1/DAZ2 are sufficient to promote G2- to M-phase transition and germ cell division in the absence of DUO1. DAZ1/DAZ2 are also required for DUO1-dependent cell differentiation and are essential for gamete fusion at fertilization. We demonstrate that the two EAR motifs in DAZ1/DAZ2 mediate their function in the male germline and are required for transcriptional repression and for physical interaction with the corepressor TOPLESS. Our findings uncover an essential module in a regulatory hierarchy that drives mitotic transition in male germ cells and implicates gene repression pathways in sperm cell formation and fertility.